PERTUMBUHAN MODAL SENDIRI PADA INDUSTRI MANUFAKTUR: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Astuti Yuli Setyani (Jurnal Riset Akuntansi dan Keuangan, 2010)
Equity Growth is influenced by internal and external factors. Internal factor under control management, i.e. return on asset (ROA), dept to equity ratio (DER) retention rate (RR). The purpose of this study is to examine the effect of internal factors toward equity growth. Using financial data of campanies listed in Jakarta Stock Exchange (JSE) from the periods of 2004 to 2008, this study finds that return on asset influence equity growth. Meanwhile, Debt to Equity Ratio and Ratention Rate show no such effect. Kata kunci:  Return On Asset, Debt to EquityRatio, Ratention Rate, Equity Growth